In search of a pedagogy of affections and a meditation-play (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Reflections on experiences in the intertwining between Theater and Spirituality, covering the fields of Pedagogy and the Scene - both seen as fertile territories for the unleashing of processes of self-knowledge that reverberate in the convivial relationships, perceptions and acts of creation. A pedagogy of affections is envisioned and the scene as a devotional act, as a contemplative practice, as a meditation-play.
Keywords: Theater and Spirituality; Pedagogy of Affections; Contemplative Practices; Meditation-play